2022
DOI: 10.1155/2022/9126699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er, Cr: YSGG Laser on Shear Bond Strength of the Orthodontic Brackets for 5 and 10 Seconds: An In Vitro Study

Abstract: Objectives. The study designed to compare the effect of erbium, chromium: yttrium-scandium-gallium-garnet (Er, Cr: YSGG) laser at different power outputs and short periods of time (5 and 10 s) and acid etching on the shear bond strength (SBS) and failure mode of metallic orthodontic brackets. Material and methods. A total of sixty-nine human premolars extracted for orthodontic purposes were used. 60 teeth were randomly assigned to one of the five treatment groups. (n = 12): group 1: 37% phosphoric acid etching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another important factor that intervenes is the morphology of the base of the brackets and the structural characteristics of the enamel. 28 , 29 In this regard, a third study found no differences in the morphology of the enamel for whitening toothpaste, 8 where the same brackets from the two previous studies were used, but evaluating human enamel with a control medium such as saliva that may have some effect on enamel remineralization. 28 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Another important factor that intervenes is the morphology of the base of the brackets and the structural characteristics of the enamel. 28 , 29 In this regard, a third study found no differences in the morphology of the enamel for whitening toothpaste, 8 where the same brackets from the two previous studies were used, but evaluating human enamel with a control medium such as saliva that may have some effect on enamel remineralization. 28 …”
Section: Discussionmentioning
confidence: 95%
“…Adhesive remnant analysis is performed to reinforce the evaluation of resistance to shear forces, using the adhesive remnant index (ARI). 29 In two included studies, whitening toothpastes with high abrasiveness frequently had ARI values ​​of 2 and 3, 18 , 20 that is, at least half of the adhesive cement remains in the bovine enamel after removal. An important factor to consider is the use of phosphoric acid in conventional adhesion systems, which increases the adhesive remnant in the enamel, 29 as occurred in the two included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the wattage of the laser irradiation also played a crucial role in altering the bond strength of the brackets. Bhagwan et al discovered that laser irradiation at a power of 2 and 2.5 W for 10 seconds was more potent than acid etching and sufficient to etch enamel [ 20 ]. This result was in line with research by Usmez and Aykent [ 21 ] and Berk et al [ 22 ], who compared the bonding efficiency using the Er,Cr:YSGG laser with a power of 1 Watt for a time period of 15 seconds and had discovered that it was substantially less than conventional acid etching [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%